The professional training of teachers: an old problem from a new angle - Marafelli, Cecilia Maria (2017)
This article aims to address the professional training of teachers from the angle of the sociology of the professions. The representation of teaching as a “vocation” and the premises of the natural, feminine tendency to perform an activity “greater” than – and superior to – other professions, that of the “educator”, has brought a tremendous ambiguity to the training of teachers. Our hypothesis is that the spread of this perspective has contributed to the professional misrepresentation of teaching. Professionalism is a necessary condition for the quality of professional practice because, when anchored in professional habitus, it enables the development of reasonable actions (“sense of play”) that, incorporated into the actions experienced in the school field, supports good professional training.